Kesiapan Moda Transportasi dan Perencanaan Muatan terhadap Kelancaran Distribusi CBU (Completely Build Up) - Harry Purwoko; Alifa Rezki Amalia; Sinung Tri Nugroho (Institut Transportasi dan Logistik Trisakti, 2019)
This study aims at investigating the effect of transportation mode readiness and cargo planning on the smooth distribution of CBU. The data was obtained through a survey of 48 CBU logistics company employees in Jakarta with multiple regression analysis tools. The results of the study prove the hypothesis of the simultaneous influence of transportation mode readiness and load planning on the smooth distribution of the CBU, with the F count of 36.080 greater than the F table value of 3.20. In addition, there is a partial effect of transportation mode readiness variable on the distribution smoothness which is significant with t count 2.121 greater than t table 1.679 and the effect of cargo planning variable on distribution smoothness is significant with t count 5.919 greater than t table 1.679.